2020
DOI: 10.1002/cnm.3342
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow‐induced cell stimulation in bone tissue engineering changes due to interstitial tissue formation in vitro

Abstract: In tissue engineering experiments in vitro, bioreactors have been used for applying wall shear stress (WSS) on cells to regulate cellular activities. To determine the loading conditions within bioreactors and to design tissue engineering products, in silico models are used. Previous in silico studies in bone tissue engineering (BTE) focused on quantifying the WSS on cells and the influence on appositional tissue growth. However, many BTE experiments also show interstitial tissue formation (i.e., tissue infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
(108 reference statements)
1
25
0
Order By: Relevance
“…In reality, however, interstitial formation, in which the tissue is infiltrated within the pores rather than being attached on the struts surfaces is also observed in many cases ( Li et al, 2009 ) (as illustrated in Figure 3C ). The resultant WSS on cells under interstitial tissue formation was quantified and compared to appositional tissue formation ( Zhao et al, 2020b ). Distinct difference in WSS between two cases were found, even if the same amount of newly formed tissue was present.…”
Section: Effect Of Cell/tissue Growth On the Micro-mechanical Environment Within Scaffold Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, however, interstitial formation, in which the tissue is infiltrated within the pores rather than being attached on the struts surfaces is also observed in many cases ( Li et al, 2009 ) (as illustrated in Figure 3C ). The resultant WSS on cells under interstitial tissue formation was quantified and compared to appositional tissue formation ( Zhao et al, 2020b ). Distinct difference in WSS between two cases were found, even if the same amount of newly formed tissue was present.…”
Section: Effect Of Cell/tissue Growth On the Micro-mechanical Environment Within Scaffold Poresmentioning
confidence: 99%
“…5. The WSS (τ) FIGURE 3 | Illustrations of (A) cells within the scaffold in computational model, re-produced from (Jungreuthmayer et al, 2009); (B) appositional tissue growth in computational model, re-produced from (Zhao et al, 2020a); (C) interstitial tissue within unit scaffold in computational model, re-produced from (Zhao et al, 2020b).…”
Section: Tissue Growth Within Scaffold Poresmentioning
confidence: 99%
“…WSS) on cells [55]. Moreover, the tissue morphologies had a distinct influence on the resultant WSS on cells [55].…”
Section: Discussionmentioning
confidence: 97%
“…Recent computational studies have shown that cell/tissue growth within a scaffold can change the mechanical stimulation (e.g. WSS) on cells [55]. Moreover, the tissue morphologies had a distinct influence on the resultant WSS on cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the CFD analysis, a number of studies also implement a fluid structure interaction (FSI) analysis [26,33,34]. This method is used to obtain a better understanding of how differences in scaffolds (such as different geometries or pore sizes) influence the shear stress on scaffold surfaces and consequently the cell adhering to those surfaces.…”
Section: Current Applications Of Cfd In Btementioning
confidence: 99%